Effect of Sinefungin on the attachment of the parasite Leishmania to the macrophages cell line J774G8 - TZORA (Α. ΤΖΩΡΑ), A.; LAWRENCE, F.; ROBERT-GERO, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The effect of Sinefungin on the attachment of the Leishmania strains L. infantum, L. tropica and L. major to the macrophages cell line J774G8 was studied. Inhibition of the attachment to the surface of macrophages was observed to the Sinefungin sensitive strains L. tropica and L. major. This inhibition was obtained only for Sinefungin pretreated promastigotes (72 hours with 2.6 and 26 Μμ Sinefungin) when incubated with macrophages for 2 and 24 hours. After 2 h incubation period of the promastigote forms of the sensitive L. tropica with macrophages, the inhibition of the attachment was 100%, whereas for the sensitive L. major strain the inhibition was 17 and 36% at a concentration of Sinefungin 2.6 and 26 μΜ respectively. The percentage of the inhibition 24 h post infection was in the range of 52 to 77% for the L. tropica strain and from 73 to 86% for the L. major strain for promastigote pretreated with 2.6 and 26 μΜ Sinefungin respectively. Controls showed that Sinefungin was not toxic for the macrophages when used for 3 days at the above mentioned concentrations. Inhibition of the protozoa - macrophage cell line J774G8 adherence was a common finding leading us to the conclusion that Sinefungin is involved actively into that process.